2016
DOI: 10.1016/j.kint.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Renal dendritic cells sample blood-borne antigen and guide T-cell migration to the kidney by means of intravascular processes

Abstract: Bony fish are among the first vertebrates to possess an innate and adaptive immune system. In these species, the kidney has a dual function: filtering solutes similar to mammals and acting as a lymphoid organ responsible for hematopoiesis and antigen processing. Recent studies have shown that the mammalian kidney has an extensive network of mononuclear phagocytes, whose function is not fully understood. Here, we employed two-photon intravital microscopy of fluorescent reporter mice to demonstrate that renal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Furthermore, using a new GFP-reporter mouse that specifically marks the CD103 + subset on the basis of expression of Snx22 and Batf3-knockout (KO) mice, we analyzed the localization and behavior of CD103 + cDCs in vivo as well as their role in NTN. We found, surprisingly, that the dense networks of cells reported previously to be DCs on the basis of CD11c or CX3CR1-GFP reporters 19,20 are actually not ZBTB46 + cDCs. Rather, these cDCs were round and localized mostly to areas around blood vessels.…”
mentioning
confidence: 41%
See 2 more Smart Citations
“…Furthermore, using a new GFP-reporter mouse that specifically marks the CD103 + subset on the basis of expression of Snx22 and Batf3-knockout (KO) mice, we analyzed the localization and behavior of CD103 + cDCs in vivo as well as their role in NTN. We found, surprisingly, that the dense networks of cells reported previously to be DCs on the basis of CD11c or CX3CR1-GFP reporters 19,20 are actually not ZBTB46 + cDCs. Rather, these cDCs were round and localized mostly to areas around blood vessels.…”
mentioning
confidence: 41%
“…Previous studies used Cx3cr1 GFP or CD11c-YFP mice 19,20 to visualize DCs in the kidney. These studies suggested that DCs form a dense anatomic network across the kidney parenchyma.…”
Section: Multiphoton Imaging Of Kidney Dcs In Different Reporter Micementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we show that CI-AKI is a multistep process involving immune activation coordinated by resident renal phagocytes, the tubular reabsorption of contrast media, and recruited leuko-Recently, several studies employed multiphoton intravital microscopy to demonstrate essential roles for resident renal phagocytes positioned adjacent to peritubular capillaries in the immune surveillance of circulating immune complexes (9,10). The resident renal phagocytes were essential to initiate immune responses, although the exact innate molecular pathways activated within these cells were not elucidated.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, intravital microscopy has been employed to advance our understanding of the tubular, microvascular, and immunologic alterations during ischemic and septic acute kidney injury (AKI) at regional (sub-organ), cellular, and sub-cellular resolution (Sutton, Mang et al 2003, Sutton, Kelly et al 2005, Gupta, Rhodes et al 2007, Sharfuddin, Sandoval et al 2009, Imamura, Isaka et al 2010, Basile, Friedrich et al 2011, Kalakeche, Hato et al 2011, Hall, Rhodes et al 2013, Hato, Sandoval et al 2015, Nakano, Doi et al 2015, McCurley, Alimperti et al 2017). Intravital microscopy has also been helpful in elucidating alterations in the transplanted kidney (Camirand, Li et al 2011) and in the kidney during systemic and local infection (Choong, Regberg et al 2012, Yatim, Gosto et al 2016). Selected overviews of the use of intravital multiphoton microscopy for studies of renal function can be found in Dunn et al (Dunn, Sandoval et al 2002), Peti-Peterdi et al (Peti-Peterdi, Burford et al 2012), and Hall and Molitoris (Hall and Molitoris 2014).…”
Section: Commentarymentioning
confidence: 99%